Modelos para a estimativa de propriedades elásticas em materiais compósitos sanduíche de núcleo honeycomb submetidos à flexão - Arroyo, Felipe Nascimento (Universidade Federal de São Carlos, 2024)
Due to their good mechanical performance combined with a low specific weight, sandwich composite materials have been applied in various situations, especially those with a discontinuous honeycomb core geometry, which has motivated the development of research into new materials, which naturally involves the manufacturing route and subsequent characterization. Na flexão, o conhecimento do módulo de elasticidade e da rigidez à flexão do compósito são de fundamental importância para o projeto estrutural, propriedades essas que podem ser determinadas experimentalmente ou estimadas por meio de modelos matemáticos. In the estimation of elastic properties, the ASTM D7250 (2020) standard, for reasons of design safety, disregards the core's influence in the estimation (transformed section method) of bending stiffness. With the aid of structural modeling using the finite element method and statistical analysis, the main objective of this research is to propose equations for estimating the modulus of elasticity and bending stiffness of honeycomb sandwich composites, as well as estimating bending stresses (tension and compression) under service conditions (small displacements - service limit state). After validating the modeling and parametric study (1944 simulations at three and four points, obtaining 972 different results), it was possible to develop new equations with provisions (i.e., R² greater than 0% and, in some cases, greater than 70%) better than the existing equations in the literature (i.e., R² equal to 0%).
Models for estimating elastic properties in honeycomb composite materials subjected to bending
Keywords: Rigidez à flexão; Modelagem numérica; Modelos de regressão; Otimização inversa; Elementos finitos; Bending stiffness; Numerical modeling; Regression models; Inverse optimization; Finite elements; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS